2018
DOI: 10.1177/1591019918798808
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience with precipitating hydrophobic injectable liquid in cerebral arteriovenous malformations

Abstract: Background Precipitating hydrophobic injectable liquid is a newly introduced liquid embolic agent for endovascular embolization with some technical advantages over other liquid embolic agents. We present our initial experience with precipitating hydrophobic injectable liquid in the endovascular treatment of cerebral arteriovenous malformations. Methods From October 2015 to January 2018, 27 patients harbori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…To date, AVM embolization using PHIL was the focus of four clinical studies, of which all included only a limited number of patients [71][72][73][74]. These studies, which altogether included not more than 50 patients, demonstrated that PHIL is effective and safe for cerebral AVM embolization.…”
Section: Clinical Datamentioning
confidence: 99%
“…To date, AVM embolization using PHIL was the focus of four clinical studies, of which all included only a limited number of patients [71][72][73][74]. These studies, which altogether included not more than 50 patients, demonstrated that PHIL is effective and safe for cerebral AVM embolization.…”
Section: Clinical Datamentioning
confidence: 99%
“…PHIL, which is available on the market in Europe, has been described in both neuro and peripheral interventions. 40 41 PHIL also does not pose a risk for gluing a microcatheter into the artery and one study demonstrated that PHIL has a greater volume of precipitation per milliliter volume injected than Onyx, 42 suggesting less PHIL would be required to fill a vessel than Onyx. However, one histologic comparison of Onyx and PHIL found greater inflammation around PHIL comparatively, 43 although this same analysis failed to show angiogenesis and found deeper penetration of the embolic in PHIL.…”
Section: Precipitating Agentsmentioning
confidence: 99%
“…The precipitating hydrophobic injectable liquid PHIL s (Micro-Vention (Terumo Corp)) is indicated for the embolisation of the peripheral and neurovasculature, including AVMs and hypervascular tumours. [47][48][49] The liquid embolic is delivered using DMSO as the carrier solvent which on mixing with blood diffuses away as the polymeric material precipitates out of solution on contact with the aqueous environment within the vasculature to form a solid embolus. The polymer is based on a 2,4,6-triidophenol-lactide-lactide-co-glycolic acrylate and hydroxyethyl-methacrylate (HEMA) (2 : 1 monomer ratio) copolymer which is non-adhesive in nature so avoids adhesion to the microcatheter during delivery (Fig.…”
Section: Precipitating Hydrophobic Injectable Liquid (Phil S S )mentioning
confidence: 99%